KOORDINASI PEMERINTAH DALAM SINGKRONISASI DATA PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN PUJUT KABUPATEN ROKAN HILIR 2019 - Putri Azzahara; Tito Handoko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The problem that often occurs in the Family Hope Program or called PKH is that it is not well targeted in collecting data on recipients of assistance from this Family Hope Program. The out of sync data makes people complain a lot against the Social Service. There are still complaints from the community against the field coordinator because it is not right on target so that many poor people do not get PKH assistance. This problem makes the local community often comment or submit their complaints to the nearest government such as to the village head which aims for the community to be able to receive social assistance from the community PKH program as well as informing village assistants of the inappropriateness of the recipients so that the facilitators are able to reconsider.This study aims to find out how the government coordinates in synchronizing the data for the family of hope (PKH) program in the Pujud sub-district, Rokan downstream district in 2019. The research method used in this study is research with qualitative analysis.The results of this study indicate that government coordination in synchronizing PKH data is carried out by implementing Family Hope Program members consisting of the head of the PKH program field, field coordinator, sub-district coordinator to assistants. Obstacles in coordinating data synchronization of the Family Hope Program in Pujud District, Rokan Hilir Regency, namely the incompleteness of the requirements so that they are not fulfilled such as an ID card or that of a Family Card, in addition to the lack of knowledge about this information, many poor people do not receive assistance from the Family Hope Program.Keywords: Coordination, Family Hope Program (PKH)